Application of two-dimensional code technology in PLC centralized control system of coal separation plant - ZHANG Chuanwei; ZHANG Peng; XU Chao (Gong-kuang zidonghua, 2015)
In view of low correctness and efficiency of traditional manual device inspection mode of coal separation plant, a PLC centralized control system of coal separation plant was proposed which was based on two-dimensional code technology. Structure and control processing of the system were introduced as well as application scheme of two-dimensional code technology in the system. Inspectors login to inspection management system in two-dimensional code scanner and download inspection tasks, then scan two-dimensional code on the inspected device. Upper computer sends running data of the device to the two-dimensional code scanner for data display by data communication between the PLC centralized control system and database servers, so as to realize device inspection. Meanwhile, the upper computer counts inspection data to complete inspector attendance.